Is 44-hour better than 24-hour ambulatory blood pressure monitoring in hemodialysis? - Martin, Luis Cuadrado [UNESP]; Franco, Roberto Jorge da Silva [UNESP]; Gavras, I.; Matsubara, Beatriz Bojikian [UNESP]; Okoshi, Katashi [UNESP]; Zanati, S. G. [UNESP]; Caramori, J. T. [UNESP]; Barretti, Pasqual [UNESP]; Balbi, André Luis [UNESP]; Gavras, H. (Karger Publishers, 2006)
The aim of this study is to evaluate if hemodialysis (HD) patients with similar blood pressure (BP) in the whole inter-HD period could have different target organ lesions and survival if the behavior of BP differs from the first to the second day of the inter-HD period. The present study compares 44-hour ambulatory BP monitoring (ABPM) patterns in 45 HD patients. Three BP patterns emerged: group A (n = 15) had similar BPs throughout (138 ± 11/88 ± 12 in the first 22 h vs. 140 ± 11/87 ± 12 mm Hg in the second 22-hour period); group B (n = 15) had a significant systolic BP rise from the first to the second period (132 ± 15/80 ± 12 vs. 147 ± 12/86 ± 13 mm Hg, p < 0.05); group C (n = 15) had significantly higher BPs (p < 0.05) than the other 2 groups throughout the whole inter-HD period, with no significant change between the 2 halves (172 ± 14/108 ± 12 vs. 173 ± 18/109 ± 14 mm Hg). Ventricular mass and survival during the 30-month follow-up period were statistically significantly better in group A, intermediate in group B and worse in group C. The data suggest that a 44-hour ABPM is more accurate than a 24-hour one in evaluating organ lesion and prognosis in HD patients. Copyright © 2006 S. Karger AG.
Keywords: Ambulatory blood pressure monitoring; Hemodialysis; Left ventricular hypertrophy; antihypertensive agent; calcitriol; erythropoietin; adult; anuria; blood pressure monitoring; clinical article; controlled study; female; follow up; heart left ventricle; heart left ventricle hypertrophy; heart ventricle; heart ventricle volume; hemodialysis; human; hypertension; male; priority journal; prognosis; statistical significance; survival rate; systolic blood pressure; treatment duration; Adult; Aged; Algorithms; Antihypertensive Agents; Blood Pressure Monitoring, Ambulatory; Echo-Planar Imaging; Electrocardiography; Female; Heart Rate; Humans; Hypertension; Kidney Failure, Chronic; Kidney Function Tests; Male; Middle Aged; Renal Dialysis; Survival Analysis